Sports Diplomacy of Batu City Government through the Batu International Sport Tourism Festival Paragliding Accuracy League 2024 - Aziza, Dicha Khansa; Soleha, Aminatus; Utomo, Ario Bimo (Journal of Integrative International Relations, 2026)
Tourism is one of the main pillars driving regional development. Batu City, with its natural potential and supportive geographical conditions, continuously strives to strengthen its position as a leading tourist destination. This research focuses on analyzing the implementation of sports diplomacy by the Batu City Government through the organization of the Batu International Sport Tourism Festival (BISTF) Paragliding Accuracy League 2024 as a tourism promotion effort. The author uses the sports diplomacy concept by Stuart Murray, which posits sports people and sporting events as essential components for achieving diplomatic goals. This descriptive qualitative research utilizes primary data obtained through the author's direct participation in the BISTF Paragliding Accuracy League 2024, while secondary data is gathered through literature review. The results indicate that the organization of the BISTF Paragliding Accuracy League 2024, initiated by the Batu City Government, is an effective strategy to promote Batu City's natural tourism potential, introduce the rich local culture of East Java, and foster cross-cultural interaction and international collaboration. Overall, the event contributes significantly to enhancing Batu City's image and tourism appeal at both national and international levels.